The Role of Lampung Provincial Government in Controlling Plastic Waste Disposal Land - Widya Krulinasari; Tia Mayang Tika (Penerbit Goodwood, 2021)
Purpose: Plastic waste is a major threat to the environment, and the growing amount of plastic waste, particularly during the Covid-19 pandemic that has been ravaging Indonesia since the beginning of 2020, has compelled the government to implement a variety of measures to rein in the surge in plastic waste, including paying close attention to land designated for plastic waste disposal. Since 2019, residents of Lampung Province have generated more than 7,000 tons of waste per day. To ascertain the Lampung Provincial government's role in controlling land for plastic waste disposal, it is necessary to conduct this study. Research Methodology: The research method used in this study is qualitative, and the data collection method is secondary. Results: It can be concluded that the Lampung Provincial government is continuing to work on developing a system for the management of plastic waste.